Accuracy of self‐reported weight, height and body mass index among older people in Japan. Issue 9 (16th July 2020) - Yazawa, Aki; Inoue, Yosuke; Kondo, Naoki; Miyaguni, Yasuhiro; Ojima, Toshiyuki; Kondo, Katsunori; Kawachi, Ichiro
Abstract : Aim: Weight and height are usually self‐reported in population‐based epidemiological surveys. While the accuracy of self‐reports has been extensively studied in younger populations, less is known in older populations. We investigated the accuracy of self‐reported weight, height and body mass (BMI) in an older cohort in Japan, where overweight/obesity and underweight coexist. Methods: We used data from older Japanese adults (≥65 years) participating in the Japan Gerontological Evaluation Study in 2016 to 2017 (7357 men and 9271 women). Self‐report data were linked to objective data obtained from clinical examinations. Results: The mean ± standard deviation (SD) age was 74.5 ± 5.8 years, mean ± SD weight, height and BMI were 55.7 ± 10.1 kg, 156.0 ± 8.9 cm and 22.8 ± 3.1, respectively. Results showed high intraclass correlation coefficients for self‐reported and measured values (0.97 for weight; 0.96 for height). While weight/height were overestimated among men (weight by 0.096 kg; height by 0.27 cm) and women (weight by 0.18 kg; height by 0.27 cm), BMI tended to be slightly underestimated (−0.034 kg/m 2 for men; −0.037 kg/m 2 for women). However, the absolute differences between self‐reported and measured values were not negligible; people had a higher risk for both under‐ and overestimation of their BMI category with increasing age. Lower education predicted BMI overestimation, whereas lower income predicted BMI underestimation. Conclusions: Overall accuracy of self‐reported body habitus was higher in this cohort of older Japanese compared with previous reports. Nevertheless, misclassification of BMI due to the misreporting of their weight/height was more common among the oldest‐old, as well as those with lower education and income. Geriatr Gerontol Int 2020; 20: 803–810 .